Evolusi Kebudayaan Manusia: Menggali Hubungan Waktu Dan Tempat Dalam Perubahan Sosial - Mgs Hasrul Haris; Maulidya Dwi Melantika; Sofiia Muntazza; Sani Safitri (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This article discusses the evolution of human culture with a focus on the relationship between time and place in social change. The research uses a literature study approach to analyze relevant literature, identifying patterns of cultural change throughout history. The results show that cultural evolution is a dynamic process influenced by historical and geographical contexts. Each historical period has unique characteristics that influence the direction of cultural change, where technological advancement and social development play an important role in accelerating transformation. The research also found that changes in values in society are often a response to the challenges of the times or specific social movements. These findings emphasize the importance of a multidisciplinary approach in understanding cultural evolution and its relevance for policymakers in designing development programs that are sensitive to local contexts. Overall, this article provides insights into how the dynamics of time and place shape patterns of socio-cultural change, and offers perspectives for dealing with socio-cultural challenges in the modern era.